Lessons From Pediatric MDS: Approaches to Germline Predisposition to Hematologic Malignancies - Avagyan, Serine; Shimamura, Akiko (Frontiers in Oncology, 2022)
Pediatric myelodysplastic syndromes (MDS) often raise concern for an underlying germline predisposition to hematologic malignancies, referred to as germline predisposition herein. With the availability of genetic testing, it is now clear that syndromic features may be lacking in patients with germline predisposition. Many genetic lesions underlying germline predisposition may also be mutated somatically in de novo MDS and leukemias, making it critical to distinguish their germline origin. The verification of a suspected germline predisposition informs therapeutic considerations, guides monitoring pre- and post-treatment, and allows for family counseling. Presentation of MDS due to germline predisposition is not limited to children and spans a wide age range. In fact, the risk of MDS may increase with age in many germline predisposition conditions, and can present in adults who lack classical stigmata in their childhood. Furthermore, germline predisposition associated with DDX41 mutations presents with older adult-onset MDS. Although a higher proportion of pediatric patients with MDS will have a germline predisposition, the greater number of MDS diagnoses in adult patients may result in a larger overall number of those with an underlying germline predisposition. In this review, we present a framework for evaluation of germline predisposition to MDS across all ages. We discuss characteristics of personal and family history, clinical exam and laboratory findings, and integration of genetic sequencing results to assist in the diagnostic evaluation. We address the implications of a diagnosis of germline predisposition for the individual, for their care after MDS therapy and for family members. Studies of MDS with germline predisposition have provided unique insights into the pathogenesis of hematologic malignancies and mechanisms of somatic genetic rescue vs disease progression. Increasing recognition in adult patients will inform medical management and may provide potential opportunities for the prevention or interception of malignancy.